2022
DOI: 10.1021/acs.jpclett.2c01039
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Phase Transition and Luminescence Tuning of Pb-Free Cs–Cu–I Perovskites Enabled by Reaction Temperature and Polar Solvent

Abstract: Ternary Pb-free Cs−Cu−I perovskites have attracted widespread attention because of their excellent optical properties and environmentally friendly advantages. Herein, two different Pb-free ternary Cs 3 Cu 2 I 5 nanocrystals (NCs) and CsCu 2 I 3 microrods (MRs) were synthesized via a heating method. The phase and morphology transition from blue emission of Cs 3 Cu 2 I 5 NCs to yellow emission of CsCu 2 I 3 MRs could be tuned effectively by manipulating the reaction temperature, decreasing the maximum photolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…The formula is as follows: Cs 3 Cu 2 I 5 –2CsI = CsCu 2 I 3 . 31 Therefore, the small sized Cs 3 Cu 2 I 5 NCs have faster phase transition when heated and show quicker temperature response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formula is as follows: Cs 3 Cu 2 I 5 –2CsI = CsCu 2 I 3 . 31 Therefore, the small sized Cs 3 Cu 2 I 5 NCs have faster phase transition when heated and show quicker temperature response.…”
Section: Resultsmentioning
confidence: 99%
“…This response time is shorter than the thermochromic perovskites reported previously (Table S1, ESI †). 31,40,41 PL spectra were obtained on the test paper before and after heating. Before heating, there was only an emitting peak at 450 nm, and after heating, there was an emitting peak at 575 nm, which further indicated that the transition from blue-phase Cs 3 Cu 2 I 5 to yellow-phase CsCu 2 I 3 occurred after high-temperature heating.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PL intensity of orange emission gradually decreases with increasing temperature, while that of blue emission first increases and then decreases, reaching a peak at 260 K. The significant difference in PL spectra of Cs 3 Cu 2 Br 5 at 80 and 300 K indicates the presence of two different luminescent transitions in the system. According to the literature, this phenomenon may be related to phase transitions of copper-based halides, which alter their radiative transition energies . XRD measurements are performed on the samples at different temperatures to verify whether the phase transition occurs at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, this phenomenon may be related to phase transitions of copper-based halides, which alter their radiative transition energies. 35 XRD measurements are performed on the samples at different temperatures to verify whether the phase transition occurs at low temperatures. Figure 3c shows that the peak positions of the sample and the XRD card are not as accurately matched as those before, which may be attributed to zero drift.…”
Section: Resultsmentioning
confidence: 99%